2022
DOI: 10.1021/acsanm.1c04346
|View full text |Cite
|
Sign up to set email alerts
|

Heating-Induced Transformation of Anatase TiO2 Nanorods into Rock-Salt TiO Nanoparticles: Implications for Photocatalytic and Gas-Sensing Applications

Abstract: Anatase TiO 2 nanocrystals (NCs) play a vital role in photocatalytic applications due to their high catalytic activity and in gas-sensing applications due to their high chemical sensitivity. Here, we report the transformation at elevated temperature of anatase nanorods (NRs) with a length of 25 nm into rock-salt TiO nanoparticles with an average size of 9.2 ± 2.1 nm investigated by means of in situ heating in the transmission electron microscope. The NRs were completely transformed to ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Consequent thermal treatment into 10Ni-Co 3 O 4 @TiO 2 NWs-I also showed characteristic peaks of TiO 2 NWs, with an additional brookite peak observed at 30.9°. The presence of the additional brookite peak together with the anatase/brookite peaks was due to the continuous thermal treatment of the catalyst, as reported in previous studies, where calcination in air induced the transformation of anatase to brookite. , Similarly, Christoforidis et al reported that the calcination of H-titanate at 380 °C retained the 1D fibril morphology but led to the formation of the brookite phase . Nevertheless, the ternary 10Ni-7Co 3 O 4 /TiO 2 NWs-M nanocomposite prepared via the mechanical assembly method displayed the peaks of both TiO 2 NWs and Co 3 O 4 .…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Consequent thermal treatment into 10Ni-Co 3 O 4 @TiO 2 NWs-I also showed characteristic peaks of TiO 2 NWs, with an additional brookite peak observed at 30.9°. The presence of the additional brookite peak together with the anatase/brookite peaks was due to the continuous thermal treatment of the catalyst, as reported in previous studies, where calcination in air induced the transformation of anatase to brookite. , Similarly, Christoforidis et al reported that the calcination of H-titanate at 380 °C retained the 1D fibril morphology but led to the formation of the brookite phase . Nevertheless, the ternary 10Ni-7Co 3 O 4 /TiO 2 NWs-M nanocomposite prepared via the mechanical assembly method displayed the peaks of both TiO 2 NWs and Co 3 O 4 .…”
Section: Resultssupporting
confidence: 52%
“…The presence of the additional brookite peak together with the anatase/brookite peaks was due to the continuous thermal treatment of the catalyst, as reported in previous studies, where calcination in air induced the transformation of anatase to brookite. 15,16 Similarly, Christoforidis et al reported that the calcination of H-titanate at 380 °C retained the 1D fibril morphology but led to the formation of the brookite phase. 17 Nevertheless, the ternary 10Ni- According to Figure 1b, ZIF-67 is identified as a microporous material because it exhibits a type I isotherm.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray diffractograms reveal that all materials are composed of the anatase crystalline phase, which is the most photocatalytically active. The position of the peaks at 2θ = 25.4, 37.9, 48.1, 55.05, 55.2, and 62.9° correspond to the respective planes (101), (004), (200), (105), (211), and (204) of tetragonal anatase TiO 2 (JCPDS: 01-073-1754), Figure A. Using the Scherrer equation, we calculated the crystalline sizes of the photocatalysts finding 13.2, 10.3, and 9.5 nm for TNF, TGW, and TGF, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks corresponding to Fe 3 O 4 and Ag along with TiO 2 in the XRD patterns of Fe 3 O 4 @TiO 2 and Ag−Fe 3 O 4 @ TiO 2 clearly indicate their crystalline phase formation in the composite. It is revealed from the matched JCPDS data that the phase of the formed TiO 2 is anatase with a tetragonal 17,18 crystal system. The crystal structures of Fe 3 O 4 and Ag are found to be inverse cubic spinel 19 and cubic, 20 respectively.…”
Section: Structural Investigationsmentioning
confidence: 97%